Theocentric Humanism Based Learning: Strategy for Forming Students' Mental and Spiritual at MA Banat Tajul Ulum Grobogan - Panuntun, Slamet; Choirudin, Moch; Raharjo, Raharjo (JASNA : Journal For Aswaja Studies, 2025)
This study aims to analyze the implementation of theocentric humanism-based learning in shaping the mental and spiritual of students at MA Banat Tajul Ulum Grobogan, identify supporting and inhibiting factors for its implementation, and provide strategic recommendations for improving the quality of learning. The research method is a descriptive qualitative approach with data collection techniques through in-depth interviews, participatory observation, and documentation studies. Data analysis was done using thematic analysis techniques of reduction, data presentation, and conclusion extraction. The study results indicate that the theocentric humanism approach applied at MA Banat Tajul Ulum has successfully integrated humanistic and spiritual values into learning. This is reflected in increased empathy, responsibility, and tolerance of students and decreased cases of violence by 70% in the last two years. The main supporting factors for this program's success are the principal's commitment, routine training for teachers, and student involvement in activities based on spiritual values. However, the implementation of this program still faces obstacles such as limited resources, including special modules provided and limited time for intensive training. This study offers something new by developing a theocentric humanism-based learning model that integrates religious and humanistic values synergistically. This approach is relevant to building students' mental and spiritual, but can also be adopted by other educational institutions to create holistic and sustainable education. The results of this study are that learning based on theocentric humanism can be an effective solution in forming the character of religious, tolerant, and integrity students.